2011
DOI: 10.5194/acp-11-3021-2011
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical and radiative effects of aerosols on warm clouds during the Amazon biomass burning season as observed by MODIS: impacts of water vapor and land cover

Abstract: Aerosol, cloud, water vapor, and temperature profile data from the Moderate Resolution Imaging Spectroradiometer (MODIS) are utilized to examine the impact of aerosols on clouds during the Amazonian biomass burning season in Rondônia, Brazil. It is found that increasing background column water vapor (CWV) throughout this transition season between the Amazon dry and wet seasons likely exerts a strong effect on cloud properties. As a result, proper analysis of aerosol-cloud relationships requires that data be st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 71 publications
7
43
0
1
Order By: Relevance
“…For the Amazonian biomass burning season Tan Hoeve et al (2011) showed that at lower values of AOD (<0.3) cloud optical depth and AOD were positively correlated whereas at higher values of AOD they were negatively correlated. The authors postulated that positive correlations at low AOD may be due to the first aerosol indirect effect whereas negative correlations at high AOD may be due to inhibition of cloud development by absorbing aerosols or potentially due to satellite retrieval artifacts.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the Amazonian biomass burning season Tan Hoeve et al (2011) showed that at lower values of AOD (<0.3) cloud optical depth and AOD were positively correlated whereas at higher values of AOD they were negatively correlated. The authors postulated that positive correlations at low AOD may be due to the first aerosol indirect effect whereas negative correlations at high AOD may be due to inhibition of cloud development by absorbing aerosols or potentially due to satellite retrieval artifacts.…”
Section: Introductionmentioning
confidence: 98%
“…Remote sensing studies have also been used to explore the relationship between cloud (cloud fraction and cloud optical depth) and aerosol (aerosol optical depth) properties (Koren et al, 2004;Kaufman and Koren, 2006;Ten Hoeve et al, 2011). For the Amazonian biomass burning season Tan Hoeve et al (2011) showed that at lower values of AOD (<0.3) cloud optical depth and AOD were positively correlated whereas at higher values of AOD they were negatively correlated.…”
Section: Introductionmentioning
confidence: 99%
“…However, positive correlations between CDR and aerosol optical depth (AOD) have also been found in some study areas, from both observations and models, especially over land (Feingold et al, 2001;Grandey and Stier, 2010;Yuan et al, 2008). Different behaviours of CDR as a function of AOD for different AOD regimes (low or high) have been observed by, for example, Tang et al (2014) and Wang et al (2015). Feingold et al (2001) concluded that there are three kinds of CDR responses to aerosol enhancement: the CDR decreases with increasing aerosol loading followed by (1) a saturation of the value of CDR in response to high AOD, (2) a decrease in the CDR with further increasing AOD due to suppression of cloud water vapour supersaturation caused by abundant large particles, or (3) an increase in CDR with further increases in AOD due to an intense competition for vapour which evaporates the smallest droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Physically, aerosol absorption of solar radiation can evaporate or thin cloud optically (Hoeve et al, 2011), and that the decrease of CF with AOD. Thus absorption effects suppress the formation and growth of clouds.…”
Section: Relationship Between Aerosol Optical Depth and Cloud Fractionmentioning
confidence: 99%